Multiple Non-Identical Four DC Motor Synchronous Speed Control:Initial Hardware and Control Scheme - M. F., Abas; Balasubramaniam, K; N.Md., Saad (2014)
This paper highlights the initial research in controlling speed of multiple DC motors synchronously. One of the motors tested for speed control are nonidentical thus the dynamics of the motor is different. The modelling of the motor, drivers and output sensors is explained with dynamics clearly described. The control scheme used is PI control and the result showed. Although the research is in its prime, the result shows promising result